2019
DOI: 10.1002/celc.201901626
|View full text |Cite
|
Sign up to set email alerts
|

Hollow Structure VS2@Reduced Graphene Oxide (RGO) Architecture for Enhanced Sodium‐Ion Battery Performance

Abstract: As a typical two‐dimensional (2D) layered material, (vanadium disulfide) VS2 has huge potentials for application in SIBs due to its large interlayer spacing and high conductivity compared to metal oxide or other 2D materials. Reduced graphene oxide (RGO) possesses exceptional electronic properties and large specific area favoring fast electron transport and rich redox sites. In this work, VS2 hollow flower spheres and RGO nanocomposites were developed for the first time, it was synthesized using a facile solvo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 66 publications
0
23
0
Order By: Relevance
“…Experimentally it was found that the as‐prepared VS 2 maintained almost 100 % capacity retention even after 600 cycles where the applied current was 5 A g −1 . The composition of VS 2 with carbonaceous materials was also explored to enhance cyclic stability and rate capability [111i,j] . In one of such reports, Xu et al .…”
Section: Electrochemistry and Battery Performance Of Different Tmds As Li/na‐ion Battery Anodesmentioning
confidence: 99%
“…Experimentally it was found that the as‐prepared VS 2 maintained almost 100 % capacity retention even after 600 cycles where the applied current was 5 A g −1 . The composition of VS 2 with carbonaceous materials was also explored to enhance cyclic stability and rate capability [111i,j] . In one of such reports, Xu et al .…”
Section: Electrochemistry and Battery Performance Of Different Tmds As Li/na‐ion Battery Anodesmentioning
confidence: 99%
“…Many binary transition metal sulfides have already been investigated for application in SIBs such as TiS 2, , MnS, , VS 2 , , or MoS 2 , , and in most cases nanoscaled or specially modified materials like reduced graphene oxide (RGO)-composite materials were used to reach a satisfying rate and cycle stability. Ternary sulfides, on the other hand, have been studied less intensively as electrode materials in SIBs, although the use of such compounds could be beneficial.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the popular catalysts possess remarkable redox characteristics in a working Li–S system (Scheme ), and the valance state changes of the catalysts during the lithiation/delithiation process are rarely mentioned in most of Li–S catalytic works. Even if the amount of the adopted catalyst is very limited, the lithiation process will lead to chemical state changes of the catalysts and will surely impose substantial changes to the interaction toward the LiPS. For example, vanadium sulfide (VS 4 ) is a well-known catalyst in Li–S batteries, which has shown superior catalytic activity toward LiPS conversion. In the operating voltage window of Li–S batteries (1.7–2.8 V), VS 4 tends to transform into Li x VS 4 ( x = 1–3) through a solid-state lithiation process, the valence state of V and S elements will simultaneously change from V 4+ to V 5+ and from S 2 2– to S 2– . The lithiation process of VS 4 and the valance state change of S and V will all impose remarkable influence in the catalytic mechanism in the Li–S system, whereas this phenomenon is rarely mentioned in related works. ,, Such a phenomenon is also detected in the Mo 6 S 8 -catalyzed Li–S system in which a prominent interaction change toward LiPS is detected due to the lithiated state of LiMo 6 S 8 …”
Section: Introductionmentioning
confidence: 99%